Komposisi Jenis Vegetasi dan Karakteristik Kimia Tanah pada Tapak Tegakan Sengon dan Karet di Desa Gohong, Kabupaten Pulang Pisau - Setiarno Setiarno; Amelia Noviyanti; Ajun Junaedi; Wahyu Supriyati; Rosdiana Rosdiana (HUTAN TROPIKA, 2023)
Plant community structure on a site has a relationship with its soil’s chemical characteristics. The research was conducted in the area of sengon and rubber stands in the administrative area of Gohong Village, Pulang Pisau District. This study aims to describe and analyze the structure of plant communities and soil chemical characteristics on the sengon and rubber stands site in Gohong Village, Pulang Pisau District. Vegetation data were collected using the stratified plot method on 9 plots placed on each stand, while soil samples for soil chemical analysis were a composite mixture of 9 drill points from each site at two depth levels, namely 0-30cm and 31-49cm. Plants found in the study site as many as 15 species belonging to 12 family, in the site of sengon stands as many as 10 species while in the site of rubber stands as many as six species. Plant species with the highest INP in the site of sengon stands are sengon and galam in the site of rubber stands are rubber. ID values range from 0.2-1.0. The depth of the peat at the research site was measured to be <50 cm with chemical characteristics of C-Organic content <5%, which was low at 4.89-6.98%, and soil acidity was very acid (pH <4.5) with a range of pH values of 3.59-3.80 and Basa Saturation (BS) was all very low with values ranging from 1.89-3.27%. Soil N-total content varied from low to medium with values ranging from 0.14-0.41%. P-availability was very low with simultaneous values of 1.18-1.41 ppm, and 0.98, and 1.19 ppm; K-dd, Ca-dd, Mg-dd, and Na-dd values were all shallow at 0.03-0.05cmol(+).kg-1, and 0.07-0.10 cmol(+).kg-1 then Ca is 0.83-1.44 cmol(+).kg-1; then Mg is the same value of 0.10 cmol(+).kg-1, and Na is 0.05-0.11 cmol(+).kg-1, while KTK is very high with a value of 49.38-60.05 cmol(+).kg-1